Pengaruh Formalitas Pengembangan Sistem Informasi Akuntansi dan Kemampuan Teknik Personal Terhadap Kinerja Sistem Informasi Akuntansi Pada Rumah Sakit Swasta Di Denpasar - Eni Susi Ani; Ni Ketut Muliati (UNHI Press, 2022)
The performance of the accounting information system will help the hospital's operations run better. The purpose of this study was to determine the effect of the formality of developing an accounting information system and personal technical skills on the performance of an accounting information system at a private hospital in Denpasar. The population in this study were all employees of a private hospital in Denpasar, as many as 1,698 employees. The sample used was 262 employees of a private hospital in Denpasar. The sampling technique is purposive sampling, sampling with certain considerations based on the research objectives. The data analysis technique used in this study is multiple linear regression analysis, the coefficient of determination and to test the hypothesis used t test and f test using SPSS software. Based on the results of the research and discussion that have been described, it can be concluded that the variables of formality in the development of accounting information systems and personal technical skills have a positive and significant effect on the performance of accounting information systems at private hospitals in Denpasar